Talent management in relation to the development of competitive advantage in Malaysian large firms - Abdul Rauf, Ahmad Redza (2020)
One of the biggest problems faced by Companies is the management of talent as talent is considered an important factor in the success and failure of businesses. Hence the subject of Talent Management can be considered one of the most important subjects in business management where mastery of it can determine the success and failure of businesses.There is however the problem of measuring Talent Management impact to overall organization success.Hence this study will examine the Talent Management practices of large Malaysian companies and whether the practices are tied to creating Competitive Advantage. Questions explored are what are the talent management practices implemented by these companies, what are the issues they face in implementing them and the management philosophy of talent employed by these companies. Finally the study looks at whether these companies managed to develop the competitive advantage they seek through the talent management practices they implement.